AN ANALYSIS OF STUDENTS’ SPEAKING HESITATION IN EFL VIRTUAL CLASSROOM - Siti Nurul 'Ilmi; A. B. Sulthan Nurya (Institut Agama Islam Negeri (IAIN) Bone, 2023)
Speaking skill has extensively expanded in line with the advancement of online and hybrid learning. Thus, researching factors related to speaking skill in virtual setting is nowadays considered prominent. This research was to reveal types speaking hesitation, as well as factors that affect students’ speaking hesitation in virtual classroom. This research adopted qualitative descriptive method. The research was based on the observation and interview conducted in SMA Negeri 1 Bone, South Sulawesi, in May 2023. The research subjects were 35 second-grade students academic year 2022-2023. To collect the data, the researcher observed and recorded 3 meetings of English subject classroom via Zoom meeting. Following this, the researcher conducted interview to 8 students who produced the most hesitation during the observation. The data were analyzed by using qualitative data analysis technique that consisted of 3 main steps: data condensation, data display, and conclusion drawing/verification. The result showed that there are 7 types of speaking hesitation produced by students in EFL virtual classroom. They are fillers, stutters, repeats, silent pauses, false starts, interjections, and corrections. Further, 4 factors that made students hesitant to speak English in virtual classroom are nervousness, family/environment interference, lack of vocabulary, and poor network. Finding of this research was significant in expanding ideas and insight about speaking hesitation, particularly in virtual classroom.Keterampilan berbicara telah berkembang pesat seiring dengan kemajuan pembelajaran daring dan hybrid. Oleh karena itu, penelitian terhadap faktor-faktor yang berkaitan dengan keterampilan berbicara dalam setting virtual saat ini dianggap penting. Penelitian ini bertujuan untuk mengungkap jenis keragu-raguan berbicara, serta faktor-faktor yang mempengaruhi hesitasi berbicara siswa di kelas virtual. Penelitian ini menggunakan metode deskriptif kualitatif. Penelitian ini didasarkan pada observasi dan wawancara yang dilakukan di SMA Negeri 1 Bone, Sulawesi Selatan, pada bulan Mei 2023. Subjek penelitian adalah 35 siswa kelas II tahun ajaran 2022-2023. Untuk mengumpulkan data, peneliti mengamati dan mencatat 3 kali pertemuan kelas mata pelajaran bahasa Inggris melalui Zoom Meeting. Setelah itu, peneliti melakukan wawancara kepada 8 siswa yang paling banyak menimbulkan hesitasi selama observasi. Analisis data dilakukan dengan menggunakan teknik analisis data kualitatif yang terdiri dari 3 langkah utama: kondensasi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasilnya menunjukkan bahwa ada 7 jenis hesitasi berbicara yang dihasilkan oleh siswa di kelas virtual EFL. Itu adalah filler, gagap, pengulangan, jeda diam, permulaan yang salah, kata seru, dan koreksi. Lebih lanjut, 4 faktor yang membuat siswa ragu untuk berbicara bahasa Inggris di kelas virtual adalah rasa gugup, faktor keluarga/lingkungan, kurangnya kosa kata, dan jaringan yang buruk. Temuan penelitian ini signifikan dalam memperluas ide dan wawasan tentang hesitasi berbicara, khususnya di kelas virtual.